2016
DOI: 10.3133/ofr20161167
|View full text |Cite
|
Sign up to set email alerts
|

Potash—A vital agricultural nutrient sourced from geologic deposits

Abstract: This report summarizes the primary sources of potash in the United States. Potash is an essential nutrient that, along with phosphorus and nitrogen, is used as fertilizer for growing crops. Plants require sufficient potash to activate enzymes, which in turn catalyze chemical reactions important for water uptake and photosynthesis. When potassium is available in quantities necessary for healthy plant growth, disease resistance and physical quality are improved and crop yield and shelf life are increased. Potash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 12 publications
(23 reference statements)
0
15
0
Order By: Relevance
“…Table 10. The yearly replacement costs of K (based on a moving 5-year average price of U.S. $500 per metric ton of potassium chloride, KCl [27]) using the kg/y values reported in Table 11 the each of the Libyan territories and the capital and major cities.…”
Section: Nutrient Cycling: Population Demand For Major and Trace Elemmentioning
confidence: 99%
“…Table 10. The yearly replacement costs of K (based on a moving 5-year average price of U.S. $500 per metric ton of potassium chloride, KCl [27]) using the kg/y values reported in Table 11 the each of the Libyan territories and the capital and major cities.…”
Section: Nutrient Cycling: Population Demand For Major and Trace Elemmentioning
confidence: 99%
“…Potassium is an important nutrient, and Sheldrick et al (2002) reported that the depletion of K is particularly severe which results in an annual global deficit of 20 kg K ha −1 . In terms of monetary cost, this annual global deficit is valued at just over $19 ha −1 based on a moving 5-year average price of U.S. $500 per metric ton of potassium chloride (KCl) (Yager, 2016). According to Sheldrick et al (2002), soil and surface balances for potassium can vary by different regions in the world.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of monetary value, this potassium requirement would cost $34.5M each day based on FIGURE 1 | The role of atmospheric potassium deposition in the gains and losses of available soil potassium under average field conditions (adapted from Brady and Weil, 2002). a moving 5-year average price of U.S. $500 per metric ton of potassium chloride (KCl) (Yager, 2016). Given a U.S. population of 325.7 million people (2017), and a recommended daily intake of 4.7 g per person per day of K, it would require at least 1,531 metric tons/day of potassium to ensure that every person is able to meet their daily potassium requirement.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations